Research on Water Droplet Movement Characteristics in the Last Two Stages of Low-Pressure Cylinder of Steam Turbine Under Low Load Conditions - Fan, Shuangshuang; Wang, Ying; Yao, Kun; Fan, Yi; Wan, Jie; Gu, Weifei (Frontiers in Energy Research, 2021)
In the operating process of the coal-fired generation during flexible peaking regulation, the primary and secondary water droplets in the steam flowing through the last two stages of the low-pressure cylinder could influence the efficiency and safety of the steam turbine definitely. However, systematic analysis of the movement characteristics of water droplets under low-load conditions is scarcely in the existing research. Toward this end, the algebraic slip model and particle transport model mentioned in this paper are used to simulate the primary and secondary water droplets respectively. Taking a 600MW unit as a research object, the droplets motion characteristics of the last two stages were simulated within five load conditions, including 100%, 75%, 50%, 40%, and 30% THA. The results show that the diameter of the primary water droplets is smaller, ranging from 0 to 1um, during the flexible peak regulation process of the steam turbine. The deposition is mainly located at the entire moving blades and the trailing edge of the last two stator blades. With the load decreasing, the deposition effect decreases sustainably. And the larger diameters of secondary water droplets range from 10 to 300um. The erosion of secondary water droplets in the last stage is more serious than that of the second last stage for different load conditions, and the erosion of the second last stage could be negligible. The pressure face and suction face at 30% blade height of the last stage blade have been eroded most seriously. The lower the load, the worse erosion from the secondary water droplets, which poses a potential threat to the fracture of the last stage blades of the steam turbine. This study provides a certain reference value for the optimal design of steam turbine blades under flexible peak regulation.